Primera cita del desarrollo de Aleroydes proletella (Linnaeus, 1758) en plantas de tomate bajo condiciones controladas - Alonso, D.D.=700 1 Gomez, A.A.; Nombela, G.; Muñiz, M.
(Es, En)
ilus., 24 ref.
Keywords: ALEYRODES; COL; INFESTACION; CULTIVO; HORTALIZAS; ESPAÑA